Differential effects of ethanol on electrical properties of various potassium channels expressed in oocytes. - Anantharam, V; Bayley, H; Wilson, A; Treistman, SN (1992)
The effects of ethanol on a number of electrophysiological parameters were examined in 10 different voltage-gated potassium channels expressed in Xenopus oocytes. None of the channels examined was highly sensitive to ethanol, but there was significant variability among the channels tested at concentrations of ethanol of 200 mM and greater. The response to ethanol was not determined exclusively by membership in a genetic subfamily. In addition, the relative sensitivity among different channels could vary independently for different electrical parameters. For example, current amplitude in DRK1 was insensitive to ethanol, even at concentrations as high as 600 mM, whereas this was one of the more sensitive channels with respect to the kinetics of current inactivation. The opposite situation was true for ShA1. Therefore, ethanol at high concentrations may selectively perturb discrete regions of channel proteins. This is supported by the finding that removal of 318 amino acids from the cytoplasmic carboxyl terminus of DRK1 results in a channel whose current amplitude shows greater sensitivity to ethanol than does DRK1. Thus, the effects of ethanol on the channel may not be limited to interactions at the lipid-protein interface.